2016
DOI: 10.1016/j.nbd.2016.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Sestrin2 induced by hypoxia inducible factor1 alpha protects the blood-brain barrier via inhibiting VEGF after severe hypoxic-ischemic injury in neonatal rats

Abstract: Objective Hypoxic ischemic (HI) encephalopathy remains the leading cause of perinatal brain injury resulting in long term disabilities. Stabilization of blood brain barrier (BBB) after HI is an important target, therefore, in this study we aim to determine the role of sestrin2, a stress inducible protein which is elevated after various insults, on BBB stabilization after moderate and severe HI injury. Methods Rat pups underwent common carotid artery ligation followed by either 150 min (severe model) or 100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 37 publications
3
46
0
Order By: Relevance
“…Moreover, Sesn2 is also induced in response to hypoxia; simulated ischemic conditions, such as hypoxia/glucose deprivation; and cerebral ischemia (27, 28, 62). Studies suggest that Sesn2 is a target of HIF‐1α, which is rapidly activated during myocardial ischemia (12), as experiments conducted in HIF‐1α–depleted cells demonstrate an absence of, or diminished, Sesn2 expression (27, 28, 63).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Sesn2 is also induced in response to hypoxia; simulated ischemic conditions, such as hypoxia/glucose deprivation; and cerebral ischemia (27, 28, 62). Studies suggest that Sesn2 is a target of HIF‐1α, which is rapidly activated during myocardial ischemia (12), as experiments conducted in HIF‐1α–depleted cells demonstrate an absence of, or diminished, Sesn2 expression (27, 28, 63).…”
Section: Discussionmentioning
confidence: 99%
“…In rats subjects to severe hypoxic-ischemic (carotid artery ligation for 150 min), researchers found that the expression of Sesn2 and the infarct area were higher than that in sham rats and moderate hypoxic-ischemic group (carotid artery ligation for 100 min) [56]. Recombinant human Sesn2 attenuated brain infarct and edema, while silencing Sesn2 reversed these protective effects after severe hypoxic-ischemic.…”
Section: Sesns In the Nervous Systemmentioning
confidence: 99%
“…Recombinant human Sesn2 attenuated brain infarct and edema, while silencing Sesn2 reversed these protective effects after severe hypoxic-ischemic. Mechanically, Sesn2 protected against severe hypoxic-ischemic encephalopathy through attenuating the blood-brain barrier permeability via inhibiting the expression vascular endothelial growth factor and promoting the expression of junction proteins [56]. In addition, the studies from the same group revealed that Sesn2 improved the infarct volume and neurological function through activating the AMPK pathway which in turn inhibits mTOR signaling and attenuates neuron apoptosis in rat hypoxic-ischemic encephalopathy model [57].…”
Section: Sesns In the Nervous Systemmentioning
confidence: 99%
“…Nrf2 is a redox‐sensitive transcription factor that translocates to the nucleus upon oxidative stress and binds to antioxidant reaction element (ARE) within the promoter of Nrf2 target genes, such as heme oxygenase‐1 (HO‐1), to initiate gene transcription . Intriguingly, numerous studies revealed that Sestrin2 participates in the progression of cerebral ischaemia/reperfusion injury and exerts neuroprotective functions against neuronal apoptosis and oxidative stress . Therefore, Sestrin2 is a promising target for neuroprotection.…”
Section: Introductionmentioning
confidence: 99%